ANALISIS KECEPATAN MEMBACA PADA TINGKAT PEMAHAMAN ISI BACAAN SISWA KELAS V SD YPK SILO KABILOL - Yuliance Sarlota Louw; Ahmad Yulianto; Syams Kusumaningrum (Al-SAMBASY: Jurnal Kajian Pendidikan, 2025)
This study uses quantitative descriptive research because the researcher wants to present an overall picture of the phenomenon based on facts that occurred in the field during the research period, which was conducted in July. The research was conducted in the fifth grade of YPK Silo Kabilol Elementary School, Tiplol Mayalibit District, Raja Ampat Regency. Data collection in this study consisted of observation, tests, interviews, and documentation. Based on the results of observations, tests, and interviews conducted by the researcher and students in Grade V and Grade V teacher Mrs. M.W. during the fieldwork, the researcher concluded that there was no consistent correlation between the two variables. There were three different relationship patterns: 1) positive correlation in some students, 2) negative correlation with no correlation, and 3) inconsistent patterns in most students. High reading speed does not guarantee optimal comprehension. Most students (53.6%) had low reading comprehension, even though their reading speeds varied. The significant findings of this study indicate that there is no consistent correlation between reading speed and reading comprehension among fifth-grade students at SD YPK Silo Kabilol. The analysis results reveal the paradox that the student with the highest reading speed, namely Y.K with 95 words per minute, did not have the highest comprehension score in the study group. Conversely, the student with the highest comprehension score, E.K with 90 points, had a moderate reading speed of 85 words per minute. This phenomenon indicates that reading speed and reading comprehension are two different cognitive skills and require specific learning approaches to optimise both aspects simultaneously.